2011
DOI: 10.3109/02770903.2011.585411
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Development of Severe Asthma Exacerbations in Children

Abstract: In this retrospective review, severe asthma exacerbations in children are associated with a more rapid onset of symptoms and are more likely to be associated with allergens or irritants, supporting the importance of atopy in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 13 publications
1
19
0
1
Order By: Relevance
“…30,31 Previous studies reported that children taking ICSs, a marker of chronic asthma severity, are at higher risk of ICU admission for asthma exacerbation. 11,32 In agreement with these studies, we identified an independent association of the current use of ICS with the risk of ICU admission. By contrast, the observed association of female sex with a higher risk of ICU admission is discordant with a previous study 33 ; the finding warrants further investigation.…”
Section: Risk Factors For Icu Admissionsupporting
confidence: 87%
“…30,31 Previous studies reported that children taking ICSs, a marker of chronic asthma severity, are at higher risk of ICU admission for asthma exacerbation. 11,32 In agreement with these studies, we identified an independent association of the current use of ICS with the risk of ICU admission. By contrast, the observed association of female sex with a higher risk of ICU admission is discordant with a previous study 33 ; the finding warrants further investigation.…”
Section: Risk Factors For Icu Admissionsupporting
confidence: 87%
“…Therefore, race, SES, and hardship all contributed to risk for overall readmission for asthma, but they did not serve as predictors for initial severe asthma exacerbation. Other studies also have failed to find race as a risk factor for admission to the ICU (34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Yet the comparability of the index acuity scores between enrollees (42,46,47). Although a variety of risk factors for severe asthma exacerbation previously have been reported, including secondhand tobacco smoke (SHS) exposure, adolescent age, overweight, family history, sensitization to fungal antigens, and respiratory infection, the most commonly reported association is between ICU admission and atopy (6,11,12,15,37,48,49). Allergically sensitized patients in our study, specifically those with sensitization to indoor allergens, were more likely to be admitted to the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency room visits and hospital admissions due to acute asthma attacks are increased in children who are sensitized and exposed to high levels of inhalant allergens in their homes, emphasizing the importance of 'allergy' in asthma exacerbations (7). The phenotypes of childhood onset allergic asthma and early sensitization are often associated with severe asthma in adulthood (8).…”
mentioning
confidence: 99%